Psychological Conditions and Social Relations of School Dropouts - Rosada, Rehan Sapto; Lestari, Sri (Indigenous, 2022)
Abstract. This study aims to understand the psychological condition and social relations of adolescents who have dropped out of school. This research was conducted using a qualitative case study type approach. The research took place in Kalibening District, Banjarnegara Regency, Central Java. The informants in this study were five out-of-school adolescents, along with their parents, teachers, and peers, with a total of 21 people. The informants were selected using a purposive sampling technique. Data collection implemented semi-structured interview techniques. The data obtained were analyzed using thematic analysis. The results indicated that adolescents who dropped out of school have low learning motivation, are introverted, are less able to control themselves, experience anxiety, tend to surrender to circumstances, and are forced by circumstances to be economically independent. Parents who are less responsible and have low educational aspirations, student-teacher conflicts, the teacher's minimal role as a second parent at school, bad influence from friends, and bullying practices contribute to adolescents' desire to quit school. This research implied that understanding the psychological condition of adolescents and their social relations can help detect the vulnerability of adolescents to dropping out of school. Thus, psychological assistance and involving parents, teachers, and peers as a support system could help prevent the issue.Keywords: psychosocial profile; adolescents; dropout.